María Jesús Zamora Calvo, Artes Maleficorum. Brujas, magos y demonios en el Siglo de Oro, Barcelona, Calambur, 2016, 270 págs. ISBN: 978-84- 8359-362-2 - Vega, Fabían R. (2016)
Fil: Vega, Fabían R. Universidad de Buenos Aires; Argentina